Molecular review of the genus Panaspis sensu lato (Reptilia: Scincidae) in Cameroon, with special reference to the status of the proposed subgenera - Schmitz, Andreas; Ineich, Ivan; Chirio, Laurent (Zootaxa, 2005)
The scincid taxa connected to the genus Panaspis sensu lato have undergone various taxonomic changes based mainly on morphological studies in the last century, but their true relationships are still far from clear. In the present study we applied Bayesian, maximum parsimony, and maximum likelihood methods of phylogenetic inference to mitochondrial 12S rRNA and 16S rRNA gene fragments to examine the degree of genetic variation within the genus. We found considerable genetic differentiation between the different proposed subgenera. Similarly, we could show that two species considered to be part of the former subgenus Leptosiaphos are in reality genuine members of the genus Lacertaspis. Based on our results we propose the recognition of the four former subgenera as full genera, and we identify several additional, possibly subgeneric, lineages within the different newly recognized full genera.